Prevalence and clinical characteristics associated with pulmonary hypertension in African-Americans. - Gaurav Choudhary; Matthew Jankowich; Wen-Chih Wu (PLoS ONE)
Background Pulmonary hypertension (PH) is associated with increased mortality and morbidity. It is frequently associated with cardiopulmonary diseases that are prevalent in African Americans (AAs). However, the prevalence or determinants of PH in the AA population is not known. Methods We conducted a cross-sectional study to estimate the prevalence of PH (defined as trans-tricuspid gradient ≥ 35 mm Hg) and associated clinical characteristics in AAs using the Jackson Heart Study cohort (n=3,282) who underwent echocardiography and had a measurable trans-tricuspid regurgitant jet. Echocardiography is frequently used for screening for PH despite its limitations in estimating accurate PA systolic pressures. Overall and age-adjusted gender-specific prevalence were estimated and modified Poisson regression was used to identify independent clinical, spirometric, and echocardiographic characteristics associated with PH. Results The mean age of the study population was 56.1 ± 12.6 years with 67.5% female. The prevalence of PH was 6.8%, with higher prevalence in female AAs (age-adjusted prevalence: Men 4.9%, 95% CI 3.6-6.2%; Women 7.7%, 95% CI 6.6-8.8%). Pulmonary hypertension prevalence increased with age (Prevalence Ratio: 10.0, 95%CI 4.0-25.1, >65 versus <45 years old), presence of obesity, higher pulse pressure, diabetes, obstructive or restrictive spirometry pattern, and severe left heart valvular disease. Also, PH was significantly associated with left atrial size and left ventricular ejection fraction. Conclusions Pulmonary hypertension is prevalent in AAs, more in women than in men. The identified cardiopulmonary risk factors that increase the prevalence of PH may assist in diagnosis and management of these at-risk subjects in the AA population.